2001
DOI: 10.1093/auk/118.2.412
|View full text |Cite
|
Sign up to set email alerts
|

Microclimate of Tree Cavity Nests: Is it Important for Reproductive Success in Northern Flickers?

Abstract: I measured structural characteristics of 160 Northern Flicker (Colaptes auratus) nests at Riske Creek, British Columbia, and placed electronic data-loggers in a subsample of 86 nests to record internal temperatures after the flickers completed nesting. Using multiple regression, I found that the best predictors of a variety of nest-cavity temperature variables were tree health, diameter of the tree at cavity height, and orientation of the cavity. Small and dead trees showed the most extreme (maximum and minimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
126
1
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(141 citation statements)
references
References 30 publications
9
126
1
5
Order By: Relevance
“…Martin and Ghalambor (1999) found that daily temperature amplitude in cavities of North American Pygmy Nuthatch (Sitta pygmaea) located in dead substrates (McEllin, 1979;Hay and Güntert, 1983), amounted to circa 10°C. Similar daily amplitudes were recorded by Wiebe (2001) in excavated mainly dead wood cavities used previously by Northern Flicker (Colaptes auratus). These results suggest that cavities in living wood would provide better buffered thermal conditions than the cavities in dead substrates.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Martin and Ghalambor (1999) found that daily temperature amplitude in cavities of North American Pygmy Nuthatch (Sitta pygmaea) located in dead substrates (McEllin, 1979;Hay and Güntert, 1983), amounted to circa 10°C. Similar daily amplitudes were recorded by Wiebe (2001) in excavated mainly dead wood cavities used previously by Northern Flicker (Colaptes auratus). These results suggest that cavities in living wood would provide better buffered thermal conditions than the cavities in dead substrates.…”
Section: Discussionsupporting
confidence: 82%
“…An identical pattern was found in all studies done during the breeding season (papers referred to above, and Stains, 1961;Martin and Ghalambor, 1999;Wiebe, 2001), as well as in studies on roosting cavities carried out during the winter (Paclík and Weidinger, 2007;Coombs et al, 2010). Thus, tree cavities appear to dampen the daily temperature fluctuations and provide a much more stable thermal environment than the world outside.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In Northern Flickers (Colaptes auratus) breeding in natural tree cavities in British Columbia, nest temperature had no effect on reproductive success (Wiebe, 2001). Although, warmer internal temperatures in artificial cavities used by American Kestrels (Falco sparverius) led to increased hatching success, the overall effect on seasonal fitness is unknown (Butler et al, 2009).…”
Section: Introductionmentioning
confidence: 99%